2017
DOI: 10.1017/s1049023x17003843
|View full text |Cite
|
Sign up to set email alerts
|

Health Service Impact from Mass Gatherings: A Systematic Literature Review

Abstract: Methods: A handheld GE V-Scan™ with Dual Probe ultrasound was available for use by physicians in the main medical tent. All treating physicians consented to participate and self-reported their training and proficiency using POCUS. After each use of POCUS, physicians completed a survey recording the indication, scans performed, and impact on diagnosis, management, and disposition of patients. Results: In total, POCUS was used on 28 patients out of the 686 patients seen in the main medical tent. The three most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…As recommended for MGE research and evaluation, data were collected to enable the reporting of event, patient presentation and outcome characteristics from the EHS, [15][16][17] as well as ED patient presentation and outcome characteristics. 7 Data were extracted from the ED Information System for the 21-day study period and included: healthcare facility (ED or EHS), age, gender, residential postcode, date and time of arrival, mode of arrival, presenting problem, assigned Australasian Triage Scale (ATS) category, International Classification of Diseases (ICD-10) group, 18 diagnosis description, time and date of discharge and discharge destination.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…As recommended for MGE research and evaluation, data were collected to enable the reporting of event, patient presentation and outcome characteristics from the EHS, [15][16][17] as well as ED patient presentation and outcome characteristics. 7 Data were extracted from the ED Information System for the 21-day study period and included: healthcare facility (ED or EHS), age, gender, residential postcode, date and time of arrival, mode of arrival, presenting problem, assigned Australasian Triage Scale (ATS) category, International Classification of Diseases (ICD-10) group, 18 diagnosis description, time and date of discharge and discharge destination.…”
Section: Data Collectionmentioning
confidence: 99%
“…These strategies may be considered in terms of: (i) specific patient groups, such as low acuity patients, 3 high acuity patients, 4 or people with mental health problem; 5 or (ii) patients requiring care at particular times such as during peak periods of ED crowding, 6 or during mass gathering events (MGEs). 7,8 A MGE is defined as an event where a group of people come together for a common purpose within a particular space or venue. In a health context, a mass gathering is an event 'where there is the potential for a delayed response to [health] emergencies', 9 due to challenges related to the environment and patient egress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic literature review exploring the health service impact from 24 different types of MGEs, variation was noted in the type of reporting of the impacts of MGEs on ambulance usage and ED visits. 3 The literature review reported that the transport to hospital rate from a MGE is approximately 1/1000 participants. 3 Furthermore, the review highlighted an absence of literature relating to the impact from MGEs on EDs beyond reporting the transport to hospital rate or raw number of patients that were transported to hospital by ambulance.…”
Section: Introductionmentioning
confidence: 99%
“…3 The literature review reported that the transport to hospital rate from a MGE is approximately 1/1000 participants. 3 Furthermore, the review highlighted an absence of literature relating to the impact from MGEs on EDs beyond reporting the transport to hospital rate or raw number of patients that were transported to hospital by ambulance. 3 From an ambulance perspective the literature is scant relating to ambulance usage at MGEs.…”
Section: Introductionmentioning
confidence: 99%